Cardiovascular disease in chronic kidney disease – a review of risk factors - Hassan, Muzamil Olamide; Oguntola, Stephen Olawale; Duarte, Raquel; Naicker, Saraladevi (African Journal of Nephrology, 2020)
Patients with chronic kidney disease (CKD) are at increased risk of cardiovascular disease (CVD), such that the risk of cardiovascular mortality is greater than the risk of progression to end-stage kidney disease. Despite the increased prevalence of traditional and non-traditional cardiovascular risk factors, patients with kidney disease have been mostly under-represented in previous cardiovascular outcome studies, thereby resulting in a paucity of data on the evidence-based management of CVD in CKD. In this review, we explore the evidence on the burden of CVD and its risk factors in patients with CKD, highlight various inflammatory biomarkers for predicting CVD and provide an overview on novel biomarkers for CVD.